Rural Agro-Tourism Potential and Economic Benefits: A Case Study of Rana Tharu Community Home Stay, Kanchanpur, Nepal - D.C., Daman Dhoj (Academia Research Journal, 2026)
Rural agro-tourism represents a promising pathway for sustainable economic development and cultural preservation in Nepal’s rural communities, where agriculture remains the primary livelihood for over 65% of the population. This case study investigates the prospects and economic impacts of agro-tourism development in the Rana Tharu Community Home Stay, located in Bhimdatta Municipality-14, Nayabasti, Kanchanpur District, in close proximity to Shuklaphata National Park. Employing a mixed-methods approach, primary data were collected through structured surveys with 30 local residents and 20 visitors, complemented by field observations and secondary sources. Results indicate that agriculture continues to be the dominant occupation (30% currently, down from 36.6% previously), with a noticeable shift toward business activities (33.3%). Tourism benefits only 30% of the local population, primarily through home stay operations and cultural experiences, while negative socio-cultural and environmental impacts remain minimal (6.7%). Visitor composition shows 75% domestic (Nepali), 20% European, and 5% American, with the majority aged 25–35 years and spending above Rs. 5,000 per visit (30%). Major attractions include Shuklaphata National Park, traditional Tharu cultural heritage, and natural landscapes. The study concludes that, despite current low penetration of tourism benefits, there exists substantial untapped potential through organic farming integration, cultural package development, and improved infrastructure. Formal registration of home stays, targeted marketing, and active involvement of local government are recommended to maximize economic returns, enhance livelihood diversification, and ensure sustainable preservation of Rana Tharu heritage. These findings contribute to the broader discourse on rural tourism as an effective tool for poverty alleviation and inclusive growth in Nepal.